Low levels of neurocognitive impairment detected in screening HIV-infected men who have sex with men: The MSM Neurocog Study. (June 2017) - Barber, TJ; Bansi, L; Pozniak, A; Asboe, D; Nelson, M; Moyle, G; Davies, N; Margetts, A; Ratcliffe, D; Catalan, J; Boffito, M; Gazzard, B
This study aimed to determine the prevalence of HIV neurocognitive impairment in HIV-infected men who have sex with men aged 18–50 years, using a simple battery of screening tests in routine clinical appointments. Those with suspected abnormalities were referred on for further assessment. The cohort was also followed up over time to look at evolving changes. HIV-infected participants were recruited at three clinical sites in London during from routine clinical visits. They could be clinician or self-referred and did not need to be symptomatic. They completed questionnaires on anxiety, depression, and memory. They were then screened using the Brief Neurocognitive Screen (BNCS) and International HIV Dementia Scale (IHDS). Two hundred and five HIV-infected subjects were recruited. Of these, 59 patients were excluded as having a mood disorder and two patients were excluded due to insufficient data, leaving 144 patients for analysis. One hundred and twenty-four (86.1%) had a normal composite z score (within 1 SD of mean) calculated for their scores on the three component tests of the BNCS. Twenty (13.9%) had an abnormal z score, of which seven (35%) were symptomatic and 13 (65%) asymptomatic. Current employment and previous educational level were significantly associated with BNCS scores. Of those referred onwards for diagnostic testing, only one participant was found to have impairment likely related to HIV infection. We were able to easily screen for mood disorders and cognitive impairment in routine clinical practice. We identified a high level of depression and anxiety in our cohort. Using simple screening tests in clinic and an onward referral process for further testing, we were not able to identify neurocognitive impairment in this cohort at levels consistent with published data.